Satellite Data Applications for Sustainable Energy Transitions - Edwards, Morgan R.; Holloway, Tracey; Pierce, R. Bradley; Blank, Lew; Broddle, Madison; Choi, Eric; Duncan, Bryan N.; Esparza, Ángel; Falchetta, Giacomo; Fritz, Meredith; Gibbs, Holly K.; Hundt, Henry; et al. (Frontiers in Sustainability, 2022)
The transition to a sustainable energy system will be one of the greatest challenges of the coming decade and beyond. New sources of information that can support decision-making are essential for this transition. A growing portfolio of satellite data products offer insights to support energy policy and planning. Here we present a review of satellite data applications in four key areas related to energy: supply, demand, impacts, and resilience. Satellite data provide greater spatial and temporal coverage in areas where other data are scarce and can complement other information sources to provide a more complete picture of the global energy system. We find that satellite data are already being applied to a wide range of energy topic areas with varying needs, from planning and operation of renewable energy projects, to tracking changing patterns in energy access and use, to monitoring environmental impacts and verifying the effectiveness of emissions reduction efforts. While satellite data can play an increased role throughout the policy and planning lifecycle, there are technical, social, and structural barriers to increased use. We conclude with a discussion of opportunities for satellite data applications to energy and recommendations for research to maximize the value of satellite data for sustainable energy transitions.